2012
DOI: 10.1681/asn.2012020181
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in Idiopathic Membranous Nephropathy

Abstract: Selective depletion of B cells with the mAb rituximab may benefit the autoimmune glomerular disease idiopathic membranous nephropathy (IMN). Here, we describe our experience treating 100 consecutive IMN patients with persistent nephrotic syndrome with rituximab. We defined complete remission as persistent proteinuria ,0.3 g/24 h and partial remission as persistent proteinuria ,3 g/24 h, each also having .50% reduction in proteinuria from baseline. During a median follow-up of 29 months after rituximab administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
222
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(242 citation statements)
references
References 46 publications
12
222
2
6
Order By: Relevance
“…These are impressive results and no serious side effects were encountered. However, four patients died, three developed cancer, and four progressed to ESRD (47). Good results with rituximab have also been reported in another observational study conducted in North America.…”
Section: What Treatment Regimens Are Effective and Safe For Patients supporting
confidence: 55%
See 1 more Smart Citation
“…These are impressive results and no serious side effects were encountered. However, four patients died, three developed cancer, and four progressed to ESRD (47). Good results with rituximab have also been reported in another observational study conducted in North America.…”
Section: What Treatment Regimens Are Effective and Safe For Patients supporting
confidence: 55%
“…Recently, these investigators reported their observational experience in 100 patients with MN treated with rituximab (47). After a mean follow-up of 29 months, 27 patients were in complete remission and 38 were in partial remission (total response rate of 65%).…”
Section: What Treatment Regimens Are Effective and Safe For Patients mentioning
confidence: 99%
“…In these patients, the duration of cyclophosphamide therapy is limited to 3 months, which results in a relatively safe cumulative dose of less than 10 g (27). Other drugs have been suggested as first-line treatment, such as mycophenolate mofetil, cyclosporin A, tacrolimus, and rituximab (28,29). Although these drugs induce remission of proteinuria, they have not been unequivocally shown to be as effective as cyclophosphamide in a direct comparison of long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although these drugs induce remission of proteinuria, they have not been unequivocally shown to be as effective as cyclophosphamide in a direct comparison of long-term outcome. Moreover, mycophenolate mofetil and calcineurin inhibitors have been associated with malignancy in the transplantation setting, possibly through viral mediators (29). For rituximab, however, data on long-term risks are limited.…”
Section: Discussionmentioning
confidence: 99%
“…While MMF as monotherapy has not been shown to be effective (23), MMF in combination with steroids may induce remissions as effectively as alkylating agents; however, posttreatment relapse occurs in 75% of patients (24). Rituximab has been shown to induce remission in several studies to date (25)(26)(27), with decline in proteinuria occurring several months after dosing. Optimal dosing regimen, retreatment schedule, and long term effects, however, are yet to be corroborated by large trials.…”
mentioning
confidence: 99%